Vagal control of the heart decreases during increasing imminence of interoceptive threat in patients with panic disorder and agoraphobia - Richter, Jan; Pietzner, Anne; Koenig, Julian; Thayer, Julian F.; Pané-Farré, Christiane A.; Gerlach, Alexander; Gloster, Andrew T.; Wittchen, Hans-Ulrich; Lang, Thomas; Alpers, Georg W.; Helbig-Lang, Sylvia; Deckert, Jürgen; et al. (Scientific reports, 2021)
Theoretically, panic disorder and agoraphobia pathology can be conceptualized as a cascade of dynamically changing defensive responses to threat cues from inside the body. Guided by this trans-diagnostic model we tested the interaction between defensive activation and vagal control as a marker of prefrontal inhibition of subcortical defensive activation. We investigated ultra-short-term changes of vagally controlled high frequency heart rate variability (HRV) during a standardized threat challenge (entrapment) in n = 232 patients with panic disorder and agoraphobia, and its interaction with various indices of defensive activation. We found a strong inverse relationship between HRV and heart rate during threat, which was stronger at the beginning of exposure. Patients with a strong increase in heart rate showed a deactivation of prefrontal vagal control while patients showing less heart rate acceleration showed an increase in vagal control. Moreover, vagal control collapsed in case of imminent threat, i.e., when body symptoms increase and seem to get out of control. In these cases of defensive action patients either fled from the situation or experienced a panic attack. Active avoidance, panic attacks, and increased sympathetic arousal are associated with an inability to maintain vagal control over the heart suggesting that teaching such regulation strategies during exposure treatment might be helpful to keep prefrontal control, particularly during the transition zone from post-encounter to circa strike defense.
Gesehen am 29.07.2021